Peer mediation conflict resolution in schools (Illinois : A Research Press, 1992)
Disscusses program background and procedures, shows sessions in which program developers train potential peer mediators and despict how peer mediators conduct the six steps in the mediation process
This video is based on the publication: Peer mediation : conflict resolutions in schools, program guide and student manual
The video is not available
Content consultant, Fred Schrumpf and Donna Crawford
Keywords: Mediation therapy; Conflict management; Problem-solving therapy; Social conflict